Congenital Lymphatic Malformation and Aortic Aneurysm in a Patient with TSC2 Mutation - Wiemer-Kruel, Adelheid; Mayer, Hans; Ewert, Peter; Martinoff, Stefan; Eckstein, Hans-Henning; Kriebel, Thomas; Bissler, John; Franz, David; Bast, Thomas (Neuropediatrics, 2020)
We present a 7-year-old boy with tuberous sclerosis and congenital segmental lymphedema (CSL) of the left leg, as well as two aortic aneurysms. He was treated with everolimus (EVE) since the age of 14 months. His CSL regressed under treatment with EVE. His first aneurysms required operative intervention at age of 17 months. Four months afterward a new aortic aneurysm had been detected above the Dracon graft, but this one remained stable since that time. The patient didn't experience severe side effects. EVE has been well tolerated without disturbance of somatic growth or serious adverse effect.
Keywords: TSC; malformations; lymphedema; aneurysm; aortic aneurysm; everolimus